Maintenance Interval Adjustment of Significant Ship Propulsion Components - Šegulja, Ivica; Bukša, Ante; Tomas, Vinko (Promet - Traffic&Transportation, 2012)
The traditional marine maintenance concept based on individual equipment manufacturer’s recommendations does not represent the most efficient maintenance strategy. Suggested manufacturer’s intervals can be modified due to a great number of factors that influence the condition and the component performance. In work [1] the model for defining and adjustment maintenance strategy onboard ships was developed, assuring the required level of safety and the lowest lifecycle cost. The present model for adjusting the maintenance interval of significant items is part of this model, which has been verified on real data from thirteen years of experience. The results obtained by the model are different from the data suggested by the manufacturer.KEYWORDS: maintenance, diesel-engine propulsion system, significant items, maintenance interval adjustment, failure rate, time between failures, maintenance interval adjustment of exhaust valve